Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
To solve the given quadratic equation:
[tex]\[ 3x^2 = 5x - 1 \][/tex]
we need to start by rewriting it in the standard quadratic form [tex]\( ax^2 + bx + c = 0 \)[/tex]. This involves bringing all terms to one side of the equation:
[tex]\[ 3x^2 - 5x + 1 = 0 \][/tex]
This standard form allows us to identify the coefficients [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex]:
[tex]\[ a = 3, \][/tex]
[tex]\[ b = -5, \][/tex]
[tex]\[ c = 1. \][/tex]
The quadratic formula to find the roots of a quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex] is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}. \][/tex]
First, we calculate the discriminant ([tex]\( \Delta \)[/tex]):
[tex]\[ \Delta = b^2 - 4ac = (-5)^2 - 4 \cdot 3 \cdot 1 = 25 - 12 = 13. \][/tex]
Next, we substitute [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( \Delta \)[/tex] back into the quadratic formula:
[tex]\[ x = \frac{-(-5) \pm \sqrt{13}}{2 \cdot 3} = \frac{5 \pm \sqrt{13}}{6}. \][/tex]
This results in the two potential solutions for [tex]\( x \)[/tex]:
[tex]\[ x_1 = \frac{5 + \sqrt{13}}{6}, \][/tex]
[tex]\[ x_2 = \frac{5 - \sqrt{13}}{6}. \][/tex]
Thus, the correct form of the solutions corresponds to option C.
Therefore, the correct choice is:
C) [tex]\( x = \frac{5 \pm \sqrt{13}}{6} \)[/tex]
[tex]\[ 3x^2 = 5x - 1 \][/tex]
we need to start by rewriting it in the standard quadratic form [tex]\( ax^2 + bx + c = 0 \)[/tex]. This involves bringing all terms to one side of the equation:
[tex]\[ 3x^2 - 5x + 1 = 0 \][/tex]
This standard form allows us to identify the coefficients [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( c \)[/tex]:
[tex]\[ a = 3, \][/tex]
[tex]\[ b = -5, \][/tex]
[tex]\[ c = 1. \][/tex]
The quadratic formula to find the roots of a quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex] is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}. \][/tex]
First, we calculate the discriminant ([tex]\( \Delta \)[/tex]):
[tex]\[ \Delta = b^2 - 4ac = (-5)^2 - 4 \cdot 3 \cdot 1 = 25 - 12 = 13. \][/tex]
Next, we substitute [tex]\( a \)[/tex], [tex]\( b \)[/tex], and [tex]\( \Delta \)[/tex] back into the quadratic formula:
[tex]\[ x = \frac{-(-5) \pm \sqrt{13}}{2 \cdot 3} = \frac{5 \pm \sqrt{13}}{6}. \][/tex]
This results in the two potential solutions for [tex]\( x \)[/tex]:
[tex]\[ x_1 = \frac{5 + \sqrt{13}}{6}, \][/tex]
[tex]\[ x_2 = \frac{5 - \sqrt{13}}{6}. \][/tex]
Thus, the correct form of the solutions corresponds to option C.
Therefore, the correct choice is:
C) [tex]\( x = \frac{5 \pm \sqrt{13}}{6} \)[/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.